Lived Experiences of COVID-19 Survivors in Nepal: A Phenomenological Analysis - Silwal, Suvekshya; Khadgi, Deepika; Mahato, Anju Kumari; Basnet, Saraswati; Thapa, Sheela; Niraula, Ashala (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: Novel coronavirus (COVID-19) is the new public health crisis rapidly threatening the world. A deeper understanding of these devastating lifetime experiences helps to develop a more complete picture of how holistic health may have been affected in survivors from pandemic. The objective of the study was to explore the lived experiences of COVID-19 survivors. Methods: A phenomenological qualitative research design was adopted following purposive sampling traced from the hospital record of Koshi Covid Hospital of Biratnagar, Province 1 Nepal. Based on principles of data saturation, ten covid survivors were interviewed following the interview guide. The obtained data were transcribed in reference to notes and tape recordings, and themes were generated. The data collection and analysis were carried out simultaneously, using thematic analysis phases of Gibson manually. Results: The study findings emerged five themes: key stakeholders in COVID-19 pandemic, mystery of COVID-19, social stigma and discrimination, mass media influence, and safety measures. Most (8/10) of the participants reported COVID-19 as mysterious disease with unknown cause and few (2/10) reported peculiar symptoms (something stuck in throat, presence of abscess in chest, etc). Seven of them faced stigmatizing responses from health care workers and most of them reported inadequate health counseling at health care institutions. Conclusions: COVID-19 survivors were scared of infecting their family and neighbors and of death related to infection. Interventions for breaking the chain of transmission were carried out, however, healthcare workers’ approach of care was inadequate along with stigma and discrimination. Adequate counseling is vital to address physical and psychological issues among survivors.